Contribution à l’étude de Ascochyta rabiei (Pass.) Labr., agent causal de l’anthracnose du pois chiche (Cicer arietinum L.) : Caractérisation morphologique et étude du pouvoir pathogène. - BENZOHRA Ibrahim Elkhalil (My University, 2009)
The work presented in this memory studies the fungus Ascochyta rabiei, agent responsible for the Ascochyta blight of chickpea, grave disease present in Algeria and in the world. Twelve isolates of Ascochyta rabiei collected various areas of the Algerian west (Sidi Bel Abbès, Mostaganem, Ain Témouchent and Mascara), used in this study, are characterized on the morphological and cultural level then their pathogenesis power studied after their inoculations on twelve lines of chickpea including seven differential lines of Kabuli type pertaining to the ICARDA (ILC 482, ILC 483, ILC 1929, ILC 7795, ILC 3279, ILC 8068 and 93-93C), a differential line of Desi type pertaining to the INRA of Versailles (INRA 199) and three local lines including two of Kabuli type (F 10-5/11 and F 1025) and another line of type Desi (F 4107). The artificial inoculations were carried out by pulverization of a inoculum (105 spores/ml) on the two weeks old seedlings. The severity of the disease was noted, two weeks after, according to the scale of Singh and al. (1981). The inoculations carried out made it possible to reproduce them the typical symptoms of the Ascochyta blight of chickpea. Thereafter, we could isole again the pathogen one starting from the sick plants of significant variety ILC 263, which thus confirms that we are in the presence of the fungus Ascochyta rabiei. The results obtained show the existence of cultural, morphological and pathogenic variability at Ascochyta rabiei. We noted that the cultural and morphological characters are not correlated with the power pathogenesis and observed that the fungus needs an incubation period from 5 to 6 days. On the other hand, the latency period lies between 8 and 10 days, because varying from an isolate to another. Concerning the evaluation of the aggressiveness of the isolates, the analysis of the results, enables us to note that the isolate Most 0208 particularly aggressive with regard to all the inoculated varieties, is followed by Msc 0208 and Msc 0308. Eight isolates are fairly aggressive: Msc 0108, Msc 0408, At 0108, At 0208, At 0308, Ad 0108, Sba 0108 and Mos 0108. The isolate Sba 0208 is not aggressive, because all the varieties inoculated by it reveal a resistance. The study of aggressiveness made it possible to highlight three levels of aggressiveness: highly aggressive isolates, fairly aggressive isolates and other the not aggressive ones. The variety F 10-5/11 is generally resistant to tolerant with all the isolates. Two varieties, ILC 3279 and ILC 8068, are tolerant with resistant for the whole of the isolates, but are sensitive to Msc 0308. INRA 199 is tolerant with ten isolates (Msc 0108, Msc 0208, Msc 0408, At 0108, At 0208, At 0308, Ad 0108, Sba 0108, Sba 0208 and Mos 0108), but sensitive to Msc 0308 and Mos 0208. Varieties ILC 7795, ILC 483, ICC 3996 and F 4107, are sensitive to four isolates and tolerant with the others. Lastly, the varieties ILC 482, ILC 1929 and F 1025, are sensitive to five isolates and tolerant with the others.
Keywords: Chickpea, Cicer arietinum, Ascochyta rabiei, morphological Characterization, pathogenesis Power.